2018
DOI: 10.1016/j.vetpar.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Low allelic diversity in vaccine candidates genes from different locations sustain hope for Fasciola hepatica immunization

Abstract: Fasciola hepatica is a trematode parasite that causes fasciolosis in animals and humans. Fasciolosis is usually treated with triclabendazole, although drug-resistant parasites have been described in several geographical locations. An alternative to drug treatment would be the use of a vaccine, although vaccination studies that have been performed mainly in ruminants over the last 30 years, show high variability in the achieved protection and are not yet ready for commercialisation. Since F. hepatica exhibits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Some of the candidate antigens include FhCL1, FhCL2, FhPrx, FhLAP and FhHDM. 95 FhLAP is one of the better studied antigens inducing protection in between 83% and 90% of livestock. [96][97][98] However, no vaccine is now commercially available and further research is needed to achieve better and sustained responses.…”
Section: Dovepressmentioning
confidence: 99%
“…Some of the candidate antigens include FhCL1, FhCL2, FhPrx, FhLAP and FhHDM. 95 FhLAP is one of the better studied antigens inducing protection in between 83% and 90% of livestock. [96][97][98] However, no vaccine is now commercially available and further research is needed to achieve better and sustained responses.…”
Section: Dovepressmentioning
confidence: 99%
“…Indeed, antigenic polymorphism has long been considered an important mechanism of immune evasion used by a number of pathogens, including helminths [ 19 ]. However, genetic analysis of several vaccine candidates (FhCL1, FhCL2, FhPrx (peroxiredoxin), FhLAP and FhHDM ( F. hepatica helminth defence molecule [ 8 ])) showed that F. hepatica exhibits only a low level of allelic variability in the sequences encoding each of these proteins amongst isolates from different geographical regions; this suggests the variability reported among vaccine studies are not related to heterogeneity in these genes, thereby reinforcing the idea that they would be suitable immunogens against liver fluke parasites globally [ 15 ]. Further elaboration of host-associated effects and the level of animal susceptibility to infection may be able to explain the variability observed in F. hepatica vaccine trials.…”
Section: Fasciolosismentioning
confidence: 98%
“…Approaches used to date to identify vaccine candidates for F. hepatica and F. gigantica include: (I) analysis of antigens that cross-react with sera from animals with other trematode infections; (II) orthologous antigens identified as vaccine candidates in other species; and (III) rational selection of antigens pivotal in liver fluke survival [ 14 ]. Many vaccine studies in livestock have evaluated the value of these candidate antigens, and Table 1 summarises the level of protective efficacy observed with some single or combination experimental F. hepatica vaccines [ 15 ]. Results of a compilation of additional efficacy trials, over the past three decades, with vaccines for both F. hepatica and F. gigantica tested in livestock, are also available [ 14 ].…”
Section: Fasciolosismentioning
confidence: 99%
See 2 more Smart Citations